Part I: Synthesis and Biological Evaluations of Potent Class L Selective Histone Deacetylase Inhibitors Part II: Aqueous Complexes for Efficient Sizebased Separation of Americium from Curium Part III: Designing Strong Chiral Bronsted Acids and Their Application for Oxaxinanones Derivatization and the Aza-henry Reaction - (:unkn) unknown (My University, 2014)
PART I: SYNTHESIS AND BIOLOGICAL EVALUATIONS OF POTENT CLASS l SELECTIVE HISTONE DEACETYLASE INHIBITORS Histone deacetylase inhibitors (HDACi) have found a wide variety of medicinal uses and are most noted for their specific apoptotic action towards cancer cells1. Several hydroxamates and tetrapeptides HDACi have since been moved on to phase 1 and 2 clinical trials, with FK228 & SAHA having already been approved for treatment of advanced cutaneous T-cell lymphoma (CTCL). FK228 & SAHA are pan-HDACi which d compounds describes the unselective inhibition for any of the 11 Zn2+-dependent HDAC isoforms. Research in the past five years, has shifted towards developing selective HDACi instead of developing pan-HDACi since they have higher cytotoxicity in vitro and vivo. The research presented involves exploration of a new class of HDACi that resemble the natural product Thailandepsin A, (TDP-A) but still retains adequate HDAC inhibitory activity and antitumor activity while increasing the maximum tolerated dose levels (MTD). Part II: AQUEOUS COMPLEXES FOR EFFICIENT SIZE-BASED SEPARATION OF AMERICIUM FROM CURIUM Separation of the adjacent actinide (An) elements americium and curium (An = Am, or Cm) is important to concepts for advanced nuclear fuel cycles proposed to reduce the transuranic content of nuclear waste placed in geological repositories,2 but the similar chemistries of Am and Cm make this separation among the most difficult in the periodic table.2 The work presented in this section examines the design and synthesis of new aqueous ligands with complexation of the adjacent actinide ions americium(III) and curium(III). The ligand N,N′-bis[6-carboxy-2-ivpyridylm-ethyl]-1,7-diaza-18crown6 (H2bp18c6) and its derivatives in an aqueous solution were studied to quantify and characterize their americium/curium selectivity. Part III: DESIGNING STRONG CHIRAL BRONSTED ACIDS AND THEIR APPLICATION FOR OXAXINANONES Nature uses chiral Brønsted acids catalytically for numerous organic reactions. Organic chemists have until only very recently realized the importance of this unique class of catalyst. As a result, there are very few known chiral Brønsted acids used in traditional asymmetric organic reactions. In recent years, due to the tremendous need for new asymmetric organic reactions in the pharmaceutical and food industries, interest in strong chiral Brønsted acids has been steadily growing. Currently, there are only a few of these acids known that have been used successfully for organic reactions. The research presented here involves exploration of a new class of chiral Brønsted acids for organic reactions. In addition, this research focuses on the importance of strong acidity as well as asymmetry for aza-Henry reaction. Binaphthyl sulfur-containing acid systems, which are analagous to sulfuric acid (H2SO4), were found to be especially attractive. This dissertation reports on the use of an innovative application of these asymmetric chiral sulfonate/sulfate systems in conjunction with a strong Brønsted acid. These new catalytic systems were very successful for obtaining asymmetry in the aza-Henry reaction.
Keywords: Bronsted Acid; Curium; Hdac; Hdaci; Histone